Crystal structure of (E)-9-({[4-(diethylamino)phenyl]imino}methyl)-2,3,6,7-tetrahydro-1H,5H-pyrido[3,2,1-ij]quinolin-8-ol - Faizi, Md. Serajul Haque (Acta Crystallogr E Crystallogr Commun, 2017)
The title compound, C(23)H(29)N(3)O, was synthesized from the condensation reaction of 8-hydroxyjulolidine-9-carbaldehyde and N,N-diethyl-p-phenylenediamine. The hydroxy group forms a intramolecular hydrogen bond to the imine N atom and generates an S(6) ring motif. The conformation about the C=N bond is E, and the aromatic ring of the julolidine moiety is inclined to the benzene ring by 3.74 (14)°. One of the fused non-aromatic rings of the julolidine moiety adopts an envelope conformation and the other has a screw-boat conformation. In the crystal, molecules are linked by C—H⋯π interactions involving the aromatic julolidine ring, forming slabs parallel to the bc plane. The tricyclic fragment of the julolidine ring and the azomethine C=N bond are disordered over two sets of sites with a refined occupancy ratio of 0.773 (3):0.227 (3).